2020
DOI: 10.1016/j.mayocpiqo.2020.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Utilization in Neurosurgery During the COVID-19 Pandemic: A Glimpse Into the Future?

Abstract: Objective: To describe telemedicine utilization in neurosurgery at a single tertiary institution to provide outpatient care during the coronavirus disease 2019 (COVID-19) pandemic, with 315 telemedicine visits performed by the neurosurgery department. Patients and Methods: In response to the COVID-19 pandemic national stay-at-home orders and postponed elective surgeries, we converted upcoming clinic visits into telemedicine visits and rescheduled other patients thought not to be markedly affected by surgical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 18 publications
(16 reference statements)
2
20
0
Order By: Relevance
“…In contrast, other care settings may see an even mix of audio-only and video telemedicine encounters. 41 Although underserved populations tend to have less access to internet and smartphones, 42,43 there is a gradual increase in smartphone ownership among these populations. 44 Our study team found that over 90% of patients seen at our free clinics self-reported smartphone ownership, 45 suggesting many patients seen should have had video capabilities on their smartphones.…”
Section: Correlates Of Telemedicine Use Among Free Clinic Patientsmentioning
confidence: 99%
“…In contrast, other care settings may see an even mix of audio-only and video telemedicine encounters. 41 Although underserved populations tend to have less access to internet and smartphones, 42,43 there is a gradual increase in smartphone ownership among these populations. 44 Our study team found that over 90% of patients seen at our free clinics self-reported smartphone ownership, 45 suggesting many patients seen should have had video capabilities on their smartphones.…”
Section: Correlates Of Telemedicine Use Among Free Clinic Patientsmentioning
confidence: 99%
“…Nonetheless, the advantages of telemedicine are met with several limitations. Most notably, there has been little change to concerns of clinical barriers for complex patients who need examination or complex interaction [ 18 , 23 , 36 , 64 ]. “Unreliability” concerns with patients down-grading signs and symptoms via telephone consultation [ 56 ] remains a challenge as consultation via telephone is a popular mode of telemedicine used by clinician and patient, which may be improved with increased video-conferencing use.…”
Section: Discussionmentioning
confidence: 99%
“… 7 Some have proposed that it may be here to stay in the future and were more hopeful in implementing it. 8 Viable long-term integration of TH will most likely involve the dedication of resources for the training of both providers and patients to reach its full potential. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Many institutions had rapidly adopted TH since the emergence of the pandemic 1 ; however, its use in neurosurgery had not been widely reported until the pandemic. 7 , 8 Understanding the benefits and challenges of using TH in a university hospital setting can provide other institutions with a practical view of whether or not to implement it.…”
Section: Introductionmentioning
confidence: 99%